EVALUATING THE EFFECT OF MEDICAL REPRESENTATIVE ON PHYSICIAN PRESCRIBING PATTERN IN IRAQ - Mikhael, Ehab Mudher (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Evaluation of the interaction between medical representatives (MRs) and physicians and the effect of such interaction on physician prescribing behavior, according to the site of view for Iraqi pharmacists. Methods: A survey for 36 pharmacists in their private pharmacies in different areas of Baghdad governorate was done through the use of a specific set of questions in a questionnaire format. Results: Most participated pharmacists agreed that physicians at most times change their prescribing pattern by attendance of the MRs, additionally there is a significant decline in the number of prescriptions for the promoted drug by the absence of medical representative for long period of time, furthermore participated pharmacists agreed that there is an irrational prescribing patterns by most physicians in Iraq. Conclusion: The interaction between MRs and physicians in Iraq, usually result in non rational prescribing patterns, which may in turn negatively affecting the health of the patients and on the other hand increases the cost of medications. Keywords: Promotion, medical representative, prescribing pattern.